Pemanfaatan Media Papan Kata dalam Meningkatkan Kemampuan Literasi Dasar dan Keaktifan Belajar Di Kelas I SDN 2 Ampenan - Saputra, Sarjan; Astawa, I Made Sujwasa; Khaer, Fikratul (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study is a Classroom Action Research (CAR) conducted at SDN 2 Ampenan with the aim of improving first-grade students’ basic literacy skills and learning activeness through the use of word-board media. The study was motivated by the low level of students’ early reading skills, as many students still struggled to recognize letters and combine them into words. The research was carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of the study were 20 first-grade students. Data collection instruments included observation sheets, field notes, and reading skill tests. The results showed an improvement in students’ reading skills from Cycle I to Cycle II. In Cycle I, 12 students (60%) achieved mastery, while 8 students (40%) had not yet met the criteria. After revisions were implemented in Cycle II, the number of students who achieved mastery increased to 17 (85%), with only 3 students (15%) remaining below the standard. In addition, the use of word-board media was found to enhance students’ learning activeness, as evidenced by increased participation, enthusiasm, and confidence during reading activities. In conclusion, the use of word-board media is effective in improving basic literacy skills as well as promoting learning activeness among first-grade students at SDN 2 Ampenan.